Find-it mall: A web-based lost and found management system for Malaysian retail environments - Nor Azmi, Siti Nur Syazlyana; Kurk, Wei Yi; Kasim, Amir Syarifuddin; Ismail, Zuriati (Research and Scientific Innovation Society, 2025)
This paper presents Find-It Mall, a web-based Lost and Found Management System designed to digitalize and streamline item recovery processes in large commercial complexes. Traditional logbook-based systems are inefficient, error-prone, and lack transparency, often leading to delayed item recovery and poor customer satisfaction. Find-It Mall addresses these challenges by integrating a centralized digital platform that connects the public and mall staff in managing lost and found items. The system features a public portal for reporting and claiming items, a staff dashboard for managing records, and an automated email notification system to enhance communication between stakeholders. Developed using PHP for server-side scripting, MySQL for database management, and Bootstrap for a responsive user interface, the system follows the Agile development methodology to ensure iterative refinement and usability. Testing results demonstrate that Find-It Mall significantly improves operational efficiency, reduces manual workload, and enhances transparency in lost and found management. The system provides a scalable, secure, and user-friendly solution that modernizes customer service standards within the Malaysian retail sector.